(untitled) (Conferencea, 2024)
In this article, the perspectives of socio-political development are of theoretical and methodological importance, and the integrative approach in researching the professional growth of teachers in continuous professional development is becoming an urgent task. The idea of interdisciplinary relations is based on the requirements of the content of educational resources, and the goal of forming qualified specialist personnel who can meet the requirements of tomorrow’s perspective, showing creative activity.